2019
DOI: 10.1111/bjd.18015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of secukinumab without the initial weekly loading dose in patients with chronic plaque psoriasis

Abstract: Summary Background Secukinumab is administered at the labelled dose of 300 mg at weeks 0, 1, 2, 3, 4 (loading dose) and every 4 weeks thereafter. Objectives To investigate the efficacy of secukinumab administered without the initial loading dose in patients with psoriasis. Methods This was a retrospective observational study including adult patients with psoriasis (n = 156) treated with secukinumab 300 mg administered either according to the labelled dose (n = 75) or without the initial loading dose (n = 81). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A GAIN study by Reich et al revealed the potential benefit of the Q2W dosing in some suboptimal responders but did not reach statistical significance compared with the Q4W dose 13 . Another therapeutic administered without the initial weekly loading dose was inferior to secukinumab at the labeled dose 14 . The feasibility of gradually increasing the dosing interval of secukinumab for treatment is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A GAIN study by Reich et al revealed the potential benefit of the Q2W dosing in some suboptimal responders but did not reach statistical significance compared with the Q4W dose 13 . Another therapeutic administered without the initial weekly loading dose was inferior to secukinumab at the labeled dose 14 . The feasibility of gradually increasing the dosing interval of secukinumab for treatment is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Another therapeutic administered without the initial weekly loading dose was inferior to secukinumab at the labeled dose. 14 The feasibility of gradually increasing the dosing interval of secukinumab for treatment is still unknown. Herein, we designed a modified therapy that gradually increases the dosing interval of secukinumab based on the response of the PASI score.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings reaffirm the association between initial weekly loading dose and treatment effectiveness. Gisondi et al 28 reported significantly greater PASI 75 and PASI 90 response rates at week 12 in psoriatic patients who received the labeled loading dose versus those who did not. The absence of loading dose was also associated with a higher proportion of primary inefficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lack of response was significantly associated with a higher body weight. However, when looking at later time points, the difference in efficacy between the two treatment groups levelled off and was insignificant from week 16 onwards until week 48 …”
mentioning
confidence: 96%
“…In this issue of the BJD , Gisondi et al . report on a retrospective observational study from Italy on the efficacy of secukinumab with or without an initial loading dose in individuals with chronic plaque‐type psoriasis . The study comprised 156 subjects who were alternately assigned to one of these two regimens.…”
mentioning
confidence: 99%